2019
DOI: 10.1108/bfj-01-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food safety training on the knowledge, practice, and attitudes of food handlers working in fast-food restaurants

Abstract: Purpose In many developing countries, the main source of food related illness is the fast foods restaurants. Health inspections of fast-food restaurants may not be sufficient to ensure and enforce the food safety regulations. The purpose of this paper is to investigate the food safety knowledge, attitudes and practices (KAP) of fast food handlers in Qatar. Design/methodology/approach Data were collected from 102 fast-food handlers through a structured survey. The questionnaire comprised questions on food saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…at is why we make our marketing campaign based on our understanding and knowledge of the range. It has been decided that Chinese consumers are not interested in the US restaurant holder because they do not offer services" [28].…”
Section: Attitude Toward Fast Foodsmentioning
confidence: 99%
“…at is why we make our marketing campaign based on our understanding and knowledge of the range. It has been decided that Chinese consumers are not interested in the US restaurant holder because they do not offer services" [28].…”
Section: Attitude Toward Fast Foodsmentioning
confidence: 99%
“…Various studies have confirmed that the training of food handlers could be effective in this regard. The success of training programs with consequent of reduction in prevalence of pathogenic microorganism in prepared foods has been established through research (Elobeid et al ., 2019 ). In developing world, food safety is indicator of economic growth that is why both government and private sector recognize the significance of safety in food supply chains (Akhtar et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latter can only be assumed based on the findings of previous studies (Roever, 2014;Samapundo et al, 2014;Kumar Gupta et al, 2017b;Asiegbu et al, 2015) since the food handlers' knowledge and BFJ 123,13 awareness were not assessed in the current study. As reported by others (Samapundo et al, 2014;Asiegbu et al, 2015;Elobeid et al, 2019), vendors and consumers are often aware of the importance of washing hands with regards to the prevention of foodborne diseases, but the majority of them have difficulties in identifying foodborne pathogens that are responsible for foodborne diseases (Hepatitis A, Salmonella spp., and Staphylococcus spp.). The existence of insufficiently educated or untrained food handlers poses a potential threat to the safety of food and its suitability for consumption (Jev snik et al, 2008).…”
Section: Street Food Vendors In Sloveniamentioning
confidence: 99%
“…Sabbithi et al (2017) established that a large number of carrot (98.1%) and onion (75.5%) samples were contaminated with E. coli during food preparation by street food handlers of Hyderabad, India. The results of the study by Elobeid et al (2019) showed that fast food handlers had poor knowledge of the proper cleaning of equipment, cross-contamination prevention, foodborne diseases, food temperature danger zone and correct procedures for thawing frozen food. Only 34.7% of the food handlers correctly identified Salmonella as a food pathogen.…”
Section: Introductionmentioning
confidence: 99%